2008
DOI: 10.1007/s10661-008-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental levels of Linear alkylbenzene Sulfonates (LAS) in sediments from the Tagus estuary (Portugal): environmental implications

Abstract: Sediments from the Tagus estuary (Portugal) were collected at 40 stations in July and December 2004. Total LAS concentrations ranged between 0.03 and 17.76 mg LAS.kg(-1) dry weight in July, and between 0.09 and 9.57 mg LAS.kg(-1) in December. Highest LAS concentrations were found at the upper northern part of the estuary, coincident with the localisation of an important waste water treatment station. According to the Predicted No Effect Concentration (PNEC) of 8.1 mg.kg(-1) derived for this compound, Environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
3
8
0
Order By: Relevance
“…2) and degradation rates consequently increase, in agreement with previous studies conducted in laboratory tests (Quiroga et al, 1999;León et al, 2004) as well as field findings (Inaba and Amano, 1988;Takada et al, 1992). However, Hampel et al (2009) recently found an inverse trend in the Tagus estuary (Portugal), which was mainly attributed to a higher dilution of the LAS input during the winter. In our case, the highest LAS concentrations were detected in the winter of 2001 and the autumn of 2002 (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…2) and degradation rates consequently increase, in agreement with previous studies conducted in laboratory tests (Quiroga et al, 1999;León et al, 2004) as well as field findings (Inaba and Amano, 1988;Takada et al, 1992). However, Hampel et al (2009) recently found an inverse trend in the Tagus estuary (Portugal), which was mainly attributed to a higher dilution of the LAS input during the winter. In our case, the highest LAS concentrations were detected in the winter of 2001 and the autumn of 2002 (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Therefore, in spite of their relatively fast degradation in the receiving waters (Scott and Jones, 2000;León et al, 2004), significant levels of LAS have been reported in aquatic ecosystems (González-Mazo et al, 1998;León et al, 2002;Lara-Martín et al, 2006;Hampel et al, 2009). Concentrations of this surfactant are often much lower in water (usually ranging from less than 1 to 100 μg L -1 ) than in sediments (up to several tens of mg kg -1 in the most contaminated areas), where LAS (especially those homologues having a longer alkyl chain) tend to be accumulated after sorption onto suspended solids, then remaining preserved fairly well under anaerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of individual compounds from the group of LAS for sediments ranged from below MDLs up to ~2100 µg kg -1 . The determined concentration of individual LAS in sediment collected in the Kłodnica catchment area is relatively similar to research conducted in Portugal (Hampel et al 2009). Moreover, the trend that a higher concentration was determined for compounds with longer alkyl chains can clearly be observed.…”
Section: Resultssupporting
confidence: 80%
“…This approach is associated with their possible impact on determined values of SAAs using the spectrophotometry technique and their differences in physicochemical properties among the groups (Ying 2006;Nomura et al 1998). In different research centers (USA, Japan, Spain, Portugal, Italy, Austria) determination of selected anionic and cationic surfactants in sediments has been conducted (OECD 2005;Hampel et al 2009;Martinez-Carballo et al 2007;Ferrer and Furlong 2002;Li and Brownawell 2010;Sun et al 2003). In Poland determination of individual surfactants has only been conducted on a relatively limited scale (mainly liquid samples).…”
Section: Introductionmentioning
confidence: 99%